Epidemiological trends of HIV/HCV coinfection in Spain, 2015–2019. Issue 7 (17th January 2022) - Fanciulli, Chiara; Berenguer, Juan; Busca, Carmen; Vivancos, María J.; Téllez, María J.; Domínguez, Lourdes; Domingo, Pere; Navarro, Jordi; Santos, Jesús; Iribarren, José A.; Morano, Luis; Artero, Arturo; et al.
Abstract: Objectives: We assessed the prevalence of anti‐hepatitis C virus (HCV) antibodies and active HCV infection (HCV‐RNA‐positive) in people living with HIV (PLWH) in Spain in 2019 and compared the results with those of four similar studies performed during 2015–2018. Methods: The study was performed in 41 centres. Sample size was estimated for an accuracy of 1%. Patients were selected by random sampling with proportional allocation. Results: The reference population comprised 41 973 PLWH, and the sample size was 1325. HCV serostatus was known in 1316 PLWH (99.3%), of whom 376 (28.6%) were HCV antibody (Ab)‐positive (78.7% were prior injection drug users); 29 were HCV‐RNA‐positive (2.2%). Of the 29 HCV‐RNA‐positive PLWH, infection was chronic in 24, it was acute/recent in one, and it was of unknown duration in four. Cirrhosis was present in 71 (5.4%) PLWH overall, three (10.3%) HCV‐RNA‐positive patients and 68 (23.4%) of those who cleared HCV after anti‐HCV therapy ( p  = 0.04). The prevalence of anti‐HCV antibodies decreased steadily from 37.7% in 2015 to 28.6% in 2019 ( p  < 0.001); the prevalence of active HCV infection decreased from 22.1% in 2015 to 2.2% in 2019 ( p  < 0.001). Uptake of anti‐HCV treatment increased from 53.9% in 2015 to 95.0% in 2019 ( p  < 0.001). Conclusions: In Spain, the prevalence of active HCV infection among PLWH at the end of 2019 was 2.2%, i.e. 90.0% lower than in 2015. Increased exposure to DAAs was probably the main reason for this sharp reduction. Despite the high coverage of treatment with direct‐acting antiviral agents, HCV‐related cirrhosis remains significant in this population.